2017
DOI: 10.3390/bioengineering4010014
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of Inorganic Nanoparticles: A Fresh Look at the Control of Shape, Size and Composition

Abstract: Several methodologies have been devised for the design of nanomaterials. The “Holy Grail” for materials scientists is the cost-effective, eco-friendly synthesis of nanomaterials with controlled sizes, shapes and compositions, as these features confer to the as-produced nanocrystals unique properties making them appropriate candidates for valuable bio-applications. The present review summarizes published data regarding the production of nanomaterials with special features via sustainable methodologies based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 116 publications
2
47
0
Order By: Relevance
“…However, in one study (Ramanathan et al, 2009), researchers demonstrated the shape of the silver nanomaterials synthesized depended on the growth kinetics of a silver resistant bacteria, Morganella psychrotolerans. Differences in the nanostructure dimensions were also dependent on the biological context of synthesis (Dahoumane et al, 2017), and here in our study, fibres derived from E. coli cultures were slightly wider and more heterogeneous in size. In a previous study, analyzing the formation of cadmium sulfide nanomaterials by E. coli only two of the four strains tested produced nanomaterials with photoluminescence (Sweeney et al, 2004), and in the same study stationary phase produced 20-fold higher nanomaterials compared with log phase cells.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…However, in one study (Ramanathan et al, 2009), researchers demonstrated the shape of the silver nanomaterials synthesized depended on the growth kinetics of a silver resistant bacteria, Morganella psychrotolerans. Differences in the nanostructure dimensions were also dependent on the biological context of synthesis (Dahoumane et al, 2017), and here in our study, fibres derived from E. coli cultures were slightly wider and more heterogeneous in size. In a previous study, analyzing the formation of cadmium sulfide nanomaterials by E. coli only two of the four strains tested produced nanomaterials with photoluminescence (Sweeney et al, 2004), and in the same study stationary phase produced 20-fold higher nanomaterials compared with log phase cells.…”
Section: Discussionsupporting
confidence: 53%
“…Mechanisms that regulate nanoparticle shape were not determined. In other contexts, the host organism influenced material shape and size (Li et al, 2011;Dahoumane et al, 2017). For example, gold nanoparticles made by Shewanella were spherical (~12 nm) in shape (Suresh et al, 2011); however, E. coli produced triangles and hexagons (Du et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the available concentrations of arsenite and sulfide, modulated by the expression level of the reduction genes, could be another potential reason for this variation in shape. Differences in the nanostructure dimensions were also dependent on the biological context of synthesis (Dahoumane et al, 2017). As shown in Figure 3, fibers derived from E. coli cultures were slightly wider and more heterogeneous.…”
Section: Discussionmentioning
confidence: 97%
“…Previous work showed the influence of the organism on material shape and size (Li et al, 2011;Dahoumane et al, 2017). Gold nanoparticles made by Shewanella were spherical (~12 nm) in shape (Suresh et al, 2011); however, E .coli produced triangles and hexagons (Du et al, 2007).…”
Section: Discussionmentioning
confidence: 99%